2014
DOI: 10.4103/2231-0762.131266
|View full text |Cite
|
Sign up to set email alerts
|

The importance of dental aesthetics among dental students assessment of knowledge

Abstract: Objective:The aim of this study is to assess the dental esthetics awareness among dental students in a private university in Chennai as none is available in Chennai, Tamil Nadu.Materials and Methods:The dental esthetics awareness questionnaire consisting of a battery of 19 questions under five aspects that is, physical, functional, social, knowledge, and psychological aspects was administered to a sample of 100 dental college students aged between 18 and 27 years in a private college in Chennai, India. Gender … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
21
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 7 publications
0
21
1
2
Order By: Relevance
“…Around two-thirds of students felt confident about their smile however almost a third reported they try to hide their smile. Manipal et al (2014) showed a higher percentage (86.2%) of females were satisfied with their smile. As for non-aesthetic restorations both this and Al-Zarea (2013) study had similar results for students reporting of having a non-aesthetic restoration in their front teeth (15.4% and 16.4% respectively).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Around two-thirds of students felt confident about their smile however almost a third reported they try to hide their smile. Manipal et al (2014) showed a higher percentage (86.2%) of females were satisfied with their smile. As for non-aesthetic restorations both this and Al-Zarea (2013) study had similar results for students reporting of having a non-aesthetic restoration in their front teeth (15.4% and 16.4% respectively).…”
Section: Discussionmentioning
confidence: 99%
“…However in the study of Manipal et al (2014) in India it was reported that the majority (86.2%) of females were satisfied with the colour of their teeth. Again these differences may be due to the fact that dental appearance is affected by individual characteristics, compliance, or unrealistic expectations (Al-Zarea 2013).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…2016 Mar;7(1):3-4 • suas relações pessoais e profissionais, o que interfere diretamente na sua autoestima. (2,3) Entre os fatores importantes que afetam a aparência dental destacam-se; a cor dos dentes, sua forma, tamanho e posição; qualidade da restauração; posição do lábio superior, visibilidade dos dentes, quantidade de exposição gengival e o alinhamento geral, especialmente dos dentes anteriores. (4) E embora cada fator possa ser considerado isoladamente, todos os componentes devem agir em conjunto para criar uma entidade harmônica e simétrica que produz o efeito final favorável à estética facial.…”
unclassified